Survival advantage with para aortic lymphadenectomy in peri-ampullary cancer: A retrospective cohort study. (July 2016) - Hafeez Bhatti, Abu Bakar; Dar, Faisal Saud; Sahaab, Eraj; Khan, Nusrat Yar; Zia, Haseeb; Rana, Atif; Salih, Muhammad; Shah, Najmul Hassan
Abstract: Background: Metastatic para aortic lymph nodes (PALN) in patients with peri ampullary cancer entail poor prognosis. Role of curative surgery in these patients remains debatable. The objective of the current study was to evaluate outcome after extended pancreaticoduodenectomy (PD) in patients with and without positive PALN. Methods: We reviewed 65 patients who underwent extended PD with PALN removal between 2011 and 2014. Patients were divided into two groups; those with positive PALN and those without. Patients were sub classified for pancreatic and non-pancreatic cancer. Outcome was determined based on median and estimated 3 year overall survival. Results: Median age was 57 (32–85) years. PALN were involved in 15 (23%) patients. Overall 3 year survival for patients with and without positive PALN was 60% and 54% (P = 0.7). Significant difference in survival was present between patients with pancreatic cancer and positive PALN [9 (3–12) months] versus non-pancreatic cancers with positive PALN [17.5 (13–38) months] (P = 0.02). Four out of five patients with pancreatic cancer and positive PALN had survival >6 months and 3 out of these 5 patients were alive at the last follow up. Conclusion: Curative surgery may benefit some patients with pancreatic cancer and positive PALN and should be considered selectively. Highlights: Should patients with peri ampullary cancer and positive PALN undergo curative surgery is debatable. Acceptable survival was demonstrated in the current study. Positive PALN should not be a contraindication to surgery in all patients.